The Effect of Board Risk Management on Financial Performance of Selected Saccos in Kiruhura District, Uganda. - Kyabarong, Benon; Agaba, Moses; Munyabonera, Francisis; Byamukama, Eliab Mpora; Kikawa, Cliff; Ahabwe, Oliver (Kabale University, 2024)
Corporate risk management and important ideas among Sacco’s in Uganda are board risk management and financial performance. The study's general objective was to determine the effect of board risk management affected the financial results of particular SACCOS in the Kiruhura District. This study used a cross-sectional survey research design using a quantitative research methodology. The sample size consisted of 184 respondents, staff, and members from the six Sacco’s registered in the Kiruhura area of Uganda as of January 2023. A total population of 342 persons was used at a confidence level of 95% or an error of 0.05. Two stages separated the data that was collected for analysis. First, SPSS version 20.0 was used to conduct the preliminary data analysis and descriptive statistics on the respondents. In the second phase, structural equation modeling (SEM) was used to evaluate and investigate the structural relationships between the variables in the proposed conceptual model. These statistics included multicollinearity, mean and standard deviation, outliers and extreme values, and missing data. SEM was implemented using Jaffrey's Amazing Statistical Program (JASP) version 0.17.2.0. The study's conclusions were: The financial performance of savings and credit co-operative societies (Sacco’s) in Uganda was found to be significantly positively impacted by board risk management (BRM) (=1.322**), boosting Ha, The study concludes that SACCOs would experience greater financial gains or better financial performance if they are more stringent about the processes they follow to review their risk profile and the policies they put in place. The study recommends that; Sacco’s risk management committees of the board should be very effective in influencing the corporate risk management practices adopted within the SACCOs and that SACCOs should improve on the levels of BRM to achieve favorable financial results by applying careful attention to governmental regulations, rules and policies.